Optimal trajectory of the neuroendoscope for third ventricle pavement access - Joana Sousa; Susana Maria Silva; Susana Maria Silva; Hélio Alves; Bruno Carvalho; Bruno Carvalho; José Maria Sousa; Manuel J. Ferreira-Pinto; Manuel J. Ferreira-Pinto; Manuel J. Ferreira-Pinto; Manuel J. Ferreira-Pinto; José Paulo Andrade; et al. (Frontiers in Neuroanatomy)
Background and aimEndoscopic Third Ventriculostomy (ETV) is used to treat hydrocephalus, an abnormal cerebrospinal fluid accumulation in brain ventricles. By defining a new trajectory and entry point interval, we aim to establish a standardized approach for FreeHand ETV, a vital technique when specialized tools are unavailable, or during emergencies.Methods187 MRIs were analyzed, with 30 having hydrocephalus. A pathway crossing the cranial bone, interventricular foramen (of Monro) and tuber cinereum was outlined. Measurements involved distances to cranial sutures, pathway angles and depths, and distances to important anatomical landmarks. Comparisons between hydrocephalic and non-hydrocephalic patients were made while assessing variations linked to age, sex and Evan’s index.ResultsSignificant differences were found, notably for depth (93.520 ± 7.228 mm), coronal plane angulation (10.982° ± 6.119°), distance to the sagittal suture (18.957 ± 8.608 mm), and distance to the superior frontal sulcus (7.00 mm). Other variables did not differ significantly between groups, including for the sagittal plane angulation (2.549° ± 3.576°) and the distances to the precentral sulcus (19.93 ± 7.955 mm), and to the coronal suture (10.55 mm).ConclusionThe new approach, situated close to cranial sutures and distant to the precentral and superior frontal sulcus, shows promise in enhancing surgical precision and outcomes for hydrocephalus management.